2020
DOI: 10.1007/s00737-020-01060-w
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-related anxiety and concerns expressed by pregnant and postpartum women—a survey among obstetricians

Abstract: This paper from India describes anxieties that pregnant and postpartum women reported to obstetricians during the COVID-19 pandemic. Of the 118 obstetricians who responded to an online survey, most had been contacted for concerns about hospital visits (72.65%), methods of protection (60.17%), the safety of the infant (52.14%), anxieties related to social media messages (40.68%) and contracting the infection (39.83%). Obstetricians felt the need for resources such as videos, websites and counselling skills to h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 14 publications
2
67
0
12
Order By: Relevance
“…Although face-to-face care from maternity and mental health services is clearly the optimum solution, Baby Buddy is in a position to provide support to expectant and new parents through its existing content, including the perinatal mental health films, the feature for couples (You and Your Partner), the Get Help feature, signposting to many other charities, and the Baby Buddy Crisis Messenger for 24/7 confidential and clinically assured support. The potential role of web-based resources in ameliorating COVID-19–related anxieties in perinatal women is echoed in a study among obstetricians in India [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although face-to-face care from maternity and mental health services is clearly the optimum solution, Baby Buddy is in a position to provide support to expectant and new parents through its existing content, including the perinatal mental health films, the feature for couples (You and Your Partner), the Get Help feature, signposting to many other charities, and the Baby Buddy Crisis Messenger for 24/7 confidential and clinically assured support. The potential role of web-based resources in ameliorating COVID-19–related anxieties in perinatal women is echoed in a study among obstetricians in India [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This COVID-19 pandemic has considerably increased global mental health issues (Druss 2020;Holmes et al 2020;Li et al 2020, b;Nanjundaswamy et al 2020;Yao et al 2020). Overall mental distress is further exacerbated by the emphasis on social distancing, and the shutdown of usual day-to-day functioning.…”
Section: Introductionmentioning
confidence: 99%
“…Only about 20% of pregnant women experience excessive concern about future events in pregnancy [6]. A study on Indian obstetricians showed that during COVID-19 pandemic the level of fear and worry were increased in pregnant women [7]. Fear, worry, and anxiety during pregnancy has negative physical and psychological health consequences for pregnant women.…”
Section: Introductionmentioning
confidence: 99%